Drug Delivery: Biocompatible Reactive Oxygen Species (ROS)‐Responsive Nanoparticles as Superior Drug Delivery Vehicles (Adv. Healthcare Mater. 1/2015). Issue 1 (January 2015) - Zhang, Dinglin; Wei, Yanling; Chen, Kai; Zhang, Xiangjun; Xu, Xiaoqiu; Shi, Qing; Han, Songling; Chen, Xin; Gong, Hao; Li, Xiaohui; Zhang, Jianxiang
<x xml:space="preserve">Abstract</x> A superior reactive oxygen species (ROS)‐responsive nanoplatform can be successfully manufactured from novel ROS‐triggerable ß‐cyclodextrin materials by X. H. Li, J. X. Zhang, and co‐workers on page 69 and may serve as a new generation drug delivery vehicle with well defined ROS‐sensitivity and excellent biocompatibility. This nanocarrier can be used for ROS‐triggered transport of diverse therapeutics and imaging agents. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>